Penerapan Metode Digital Marketing Pada Mixue Rengasdengklok - Meiliana Halim; Gabriel Matius Wijaya; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The purpose of this industrial visit in the Mixue Rengasdengklok is: 1. To know types of digital marketing 2. To know the digital marketing methods carried out by Mixue Rengasdengklok. This type of research used is descriptive with observative. The results we obtained from the visits that we have already done, among other things, know the marketing done by Mixue itself. Social media is very important as one of the tools (digital marketing) carried out by Mixue Rengasdengklok to start its first business, because the time used more effectively and efficiently does not waste a lot of time, does not require a large capital to make a brochure and does not spend a great deal of energy to share the brochures. Social media can be used as one of the digital tools to do a promotion or advertise most of the products of the business itself. In the content of Mixue there is unique content and managed to draw the attention of the public to its products. The uniqueness and quality of the content associated with the product has resulted in positive reviews.